Haptic display of micro surface undulation based on discrete mechanical stimuli to whole fingers. (16th February 2017) - Tanaka, Y.; Goto, Y.; Sano, A.
Graphical Abstract: Abstract : Humans can perceive a wide and small surface undulation that is hundreds micrometers in height and hundreds millimeters in width by scanning the surface with their whole fingers and palm in the distal and proximal directions. We developed a wearable haptic device that presents a surface undulation to the hand. The device is composed of nine independent stimulator units that control the heights of nine finger pads of the index finger, the middle finger, and the ring finger (three units on each finger) according to the virtual surface. Three experiments are carried out to evaluate the haptic perception by the haptic device. A first experiment shows that the perceived dimensions are diminished as compared to the dimensions applied by the haptic device. On the basis of this result, the applied dimensions are calibrated to match the virtual surface undulation to the real surface undulation. A second experiment shows that the shape of gently-curved surfaces can be estimated with the haptic display. A third experiment shows that the discrimination threshold is not different between the virtual surface undulation and the real surface undulation. These experimental results show the applicability of the haptic device as a haptic interface.